Epistemologi Pendidikan Dasar Islam - Dea Rakhimafa Wulandari; Resti Fitriati (Pendidikan Guru Madrasah Ibtidaiyah, Universitas Nahdlatul Ulama Purwokerto, 2025)
This article aims to discuss the concept of epistemology of Islamic basic education, which has recently become an intellectual discourse of Islamic education that is being sought for its ideal formulation, along with the rapid development of science and technology, methodology, and socio-cultural problems that need to be enlightened from the world of Islamic education in particular. Epistemology, as one of the components of philosophy related to science, especially concerning the ways, processes, and procedures of how knowledge is obtained. The epistemological sources of Islamic basic education are the Quran, Hadits, and Ijtihad. The epistemological methods of Islamic basic education include the rational method, the intuitive method, the dialogical method, the comparative method, and the critical method.